Analisis Respon Guru Terhadap Sosialisasi dan Pelatihan Pemanfaatan Aplikasi Canva dalam membuat Media Pembelajaran di SDN 004 Muaro Sentajo - Fadillah Fadillah (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Current technological advances should be able to make teachers innovate in teaching. In order to create interactive learning, teachers should use learning media by utilizing technology, such as using the Canva application. The aim of this research is to analyze teachers' responses to socialization and training on the use of the Canva application in creating interesting and interactive learning media for students. This research was carried out at SDN 004 Muaro Sentajo using quantitative research with a pre-experimental design experimental approach with a one shot case study type. Data collection techniques through questionnaires, observation, interviews and documentation. The research instrument used a questionnaire and data analysis techniques used 5 LikeArt scale categories. The 5 categories were grouped into 2 responses, namely negative and positive responses, then the average was found. So based on the research results, the average percentage of teacher responses was 95.7% with a positive value and 4.2% with a negative value.